Determination of eutrophic areas in Mundaú/Manguaba lagoons, Alagoas-Brazil, through studies of the phytoplanktonic community - Melo-Magalhães,EM. (2009)
Mundaú and Manguaba Lagoons (9° 34' 38"-9° 45' 30" S and 35° 44' 00"-35° 58' 13" W) are considered the largest and most productive ones in the state of Alagoas and were studied with the purpose of identifying the existence of anthropic impacts. Samples were collected at 8 stations, during low tide and flooding in rainy and dry periods, using the "Van Dorn" bottle and plankton net. In total, 155 taxons were identified, with special emphasis on Bacillariophyta and Cyanophyta divisions. The most abundant species in Mundaú Lagoon was Skeletonema cf. costatum, and in the Manguaba Lagoon, Cyclotella meneghiniana, Microcystis aeruginosa and Anabaena spiroides. The diversity ranged from 0.17 bits cell/L to 4.81 bits cell/L. The predominance of freshwater species (51%), evidenced higher influence of the limnetic flow on the two environments studied. The high values related to the phytoplanktonic density characterize the lagoons as strongly impacted environments, indicating the existence of eutrophic conditions in most of the studied stations.